Pengaruh Penambahan Active Cycle Of Breathing Technique pada Terapi Inhalasi Dalam Mengurangi Derajat Sesak Nafas Pada Penderita Asma Bronkhial - Jeffry, Rachmat; , Isnaini Herawati, S.Fis.,Ftr.,M.Sc; , Dwi Rosella K, S.Fis.,Ftr.,M.Fis (2015)
Background: Bronchial asthma is a chronic respiratory system disease with signs of repeated attacks and difficulty of breathing, wheezing, and coughs. During the attack, bronchus is experiencing convulsion so that it becomes narrower and unable to release air sufficiently from lungs. Ventolin is a preparation of inhaler cough medicine consisting of 3 elements, namely H2O and O¬2 putting into a nebulizer to be changed into gas and it can be inhaled. The use of Ventolin with nebulizer device is more effective in relieving cough and thinning thick mucus obstructing respiratory tract. Ventolin-nebulizer is a device to change liquid medicine into aerosol so that it can be inhaled easily into lungs. Active Cycle of Breathing Technique (ACBT) is a breathing technique combined with breathing control, deep breathing, and huffing in order to control a breathing pattern to approach normal breathing one so that it can relieve asphyxia, reduce frequency of asphyxia, and improve posture. Purpose of the Research: Purpose of the research is to know addition of Active Cycle of Breathing Technique (ACBT) in a ventolin-nebulizer inhalation therapy in order to relieve asphyxia degree of asthma patient. Method of the Research: The research is a quasi-experimental one with pretest and posttest two groups design. Sample meeting inclusion and exclusion criteria were 26 respondents. The sample was divided into two groups. A control group consisted of 13 respondents and a treatment group consisted of 13 respondents. Results of the Research: Based on Wilcoxon test, the control group with no Active Cycle of Breathing Technique obtained value of p < 0.05 meaning that a significant result, whereas the treatment group with addition of Active Cycle of Breathing Technique had value of p < 0.05. Consequently, Ho is rejected and Ha is accepted because it means that addition of Active Cycle of Breathing Technique has effect on relieving asphyxia degree of bronchial asthma patient. Results of Mann-Whitney analysis for control group and treatment group obtained p = 0.049 or p < 0.05 so that Ho is rejected and Ha is accepted. It means a different effect between control group and treatment group caused by the addition of Active Cycle of Breathing Technique in Ventolin-Nebulizer inhalation therapy on relieving asphyxia degree of bronchial asthma patient. Conclusion: Different effect between control group and treatment group caused by the addition of Active Cycle of Breathing Technique in Ventolin-Nebulizer inhalation therapy on relieving asphyxia degree of bronchial asthma patient was found.